Hyperglycaemia disrupts conducted vasodilation in the resistance vasculature of db/db mice - Lemmey, H; Ye, X; Ding, H; Triggle, C; Garland, C; Dora, K (Elsevier, 2018)
Vascular dysfunction in small resistance arteries is observed during chronic elevations in blood glucose. Hyperglycaemia-associated effects on endothelium-dependent vasodilation have been well characterized, but effects on conducted vasodilation in the resistance vasculature are not known. Small mesenteric arteries were isolated from healthy and diabetic db/db mice, which were used as a model of chronic hyperglycaemia. Endothelium-dependent vasodilation via the Gq/11-coupled proteinase activated receptor 2 (PAR2) was stimulated with the selective agonist SLIGRL. The Ca2 +-sensitive fluorescent indicator fluo-8 reported changes in endothelial cell (EC) [Ca2 +]i, and triple cannulated bifurcating mesenteric arteries were used to study conducted vasodilation. Chronic hyperglycaemia did not affect either EC Ca2 + or local vasodilation to SLIGRL. However, both acute and chronic exposure to high glucose or the mannitol osmotic control attenuated conducted vasodilation to 10 μM SLIGRL. This investigation demonstrates for the first time that a hypertonic solution containing glucose or mannitol can interfere with the spread of a hyperpolarizing current along the endothelium in a physiological setting. Our findings reiterate the importance of studying the effects of hyperglycaemia in the vasculature, and provide the basis for further studies regarding the modulation of junctional proteins involved in cell to cell communication by diseases such as diabetes.